Tuberculosis in the era of anti-TNF-alpha therapy: Why does the risk still exist? - John Leonardo Torres-Castiblanco (Biomédica, 2018)
Rheumatoid arthritis is an autoimmune systemic disease characterized mainly by inflammatory compromise of diarthrodial joints. Multiple drug therapies have been developed to control the activity of rheumatoid arthritis, among them, the first line of disease-modifying antirheumatic drugs (DMARD), and novel drug therapies such as the anti-TNF alpha therapy, with satisfactory clinical outcomes.Despite this positive fact, the use of this therapy implies the risk of producing negative effects due to its mechanism of action, which has been associated with multiple infections, especially tuberculosis, making it necessary to use screen tests before resorting to this kind of drugs.We present the case of a 58-year-old female patient, with a six-year history of rheumatoid arthritis.The patient developed disseminated tuberculosis with compatible radiological and histological findings after receiving treatment with infliximab (anti-TNF therapy). No test was performed to screen for latent tuberculosis infection prior to the administration of infliximab.The performance of routine screenings tests for tuberculosis prior to anti-TNF alpha therapy plays an essential role in the detection of asymptomatic patients with latent tuberculosis. This is the only way to identify those patients who would benefit from anti-tuberculosis drugs before the initiation of anti-TNF alpha therapy, which makes the difference in the search of a significant reduction in the incidence of tuberculosis and its associated morbidity and mortality.